Caracterização e classificação de resíduos sólidos das indústrias de cerâmicas artísticas de Porto Ferreira, SP - Gomes, Araceli Cristina Prezoto (2003)
The main objective of this work is to perform the characterization of the solid wastes from some artistic ceramic industries of Porto Ferreira-SP. The so-called white ceramics are obtained with some specific type of clays and melting materials and burned in on oven 1200 1500 oC. The decoration process of the utensils is made with fried and inorganic pigments (hot ceramic) and with organic solvents, glitters and oil ink (cold ceramic). This study reveled that at the studied industries the water used at the washing process of paint brushers and other recipients or flasks is first decanted and then drained to the sewer system and/or directed poured to any water body adjacent to the industry site. The solid wastes are deposited in containers which are then transported to a garbage site of the municipality or disposed above ground in areas adjacent to the Mogi-Guaçu River. This study was based on the federal environmental legislation Resolução CONAMA 006/88 and Normas NBR 10.004 10.007 . The inventory of residues seeks to answers questions on the solid wastes such as where and the flux they are generated by an industrial process according to a mass balance of the productive process. This set of environmental regulation establishes the grounds for the waste classification through numerical values of limiting values for different chemical species that may be detected in the elutriate (solubilization test) (NBR 10.006/87) and leachate (lixiviation test) (NBR 10.005/87) extracts. These extracts were analyzed by ICP-AES (inductively coupled plasma atomic emission spectroscopy) and AAS (atomic absorption spectrofotometry) for metals and metalloids and by GC-MS (gas chromatographymass spectrometry) for organic compounds. The results of this study show that some specific type of solid wastes has concentration of metals and/or organic compounds in the solubilization and/or lixiviation extracts that are in disagreement to the federal legislation. The severity of this problem and the real necessity to undertake the present study become apparent when it is considered the existence of 108 ceramic industries in Porto Ferreira-SP. The solubilized and leachable contaminants may be reaching ground waters as well as tributaries and the Mogi-Guaçu River itself which may be adversely impacting these aquatic ecosystems.